Analisis Ketimpangan Pendapatan, Indeks Pembangunan Manusia, dan Upah Minimum Terhadap Kemiskinan di Provinsi Aceh - Eva Safrinja; Puti Andiny; Martahadi Mardhani; Safuridar Safuridar (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to analyze the effect of income inequality, human development index, and minimum wage on poverty in Aceh Province. It uses secondary data in the form of time series for the period 2009-2023, published by the Central Statistics Agency (BPS) of Aceh Province. The data analysis method employs multiple regression analysis using Eviews 10 software. The results show that income inequality has a negative and insignificant effect on poverty in Aceh Province. Furthermore, the human development index (HDI) has a negative and significant effect on poverty in Aceh Province. Meanwhile, the minimum wage has a positive and insignificant effect on poverty in Aceh Province. Simultaneously, income inequality, the human development index (HDI), and the minimum wage significantly affect poverty in Aceh Province.